Verbal Strategies of courtesy in argumentative interactions ocurring in schoolcontexts (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Oral argumentation supposes different domains, like strategies of courtesy, that make the interactive relationships easier (attenuating imposition and promoting agreement). This is why we pretend to detect the argumentation stages in the interaction and the courtesy strategies that regulate a guided situation and a spontaneous one. Also, we present key concepts about argumentation study, stages and courtesy strategies that, following Cros (2003), must be used in an oral discussion in the classroom. Ultimately, we can say that students present general problems as concessions and use cooperation strategies in both situations, they develop an extended arguing stage, planning thesis and arguments, utilizing courtesy strategiesthat minimize the threatening acts and avoid coercing the interlocutor. Finally, just in guided interaction we find the closing stage that finishes the initial disagreement.
Keywords: Oral argumentative interaction; courtesy strategies; argumentation stages